PBT (polybutylene terephthalate) composition as well as preparation method and application thereof
By adding ethylene bistetrabromophthalimide and glass fiber to the PBT resin, a PBT composition is formed, which solves the problem of aging and large chromatic difference changes in glass fiber reinforced PBT materials in the sunlight environment, and achieves good flame retardant properties and mechanical properties of the materials.
Patent Information
- Application Number
- CN202411727415.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-28
AI Technical Summary
Glass fiber reinforced PBT materials are prone to aging and degradation when exposed to strong sunlight for a long time, resulting in large changes in chromatic aberration and a decrease in surface gloss, affecting the appearance and performance of the material.
PBT resin is used as the matrix, ethylenebistetrabromophthalimide is added as a synergistic ultraviolet absorber and ultraviolet light shielding agent, and glass fibers are combined to form a PBT composition. The composition reduces chromatic aberration changes after aging by improving the flame retardant and weathering properties of the material.
The chromatic aberration changes of the PBT composition are achieved, while improving the flame retardant and mechanical properties of the material, which are suitable for products used outdoors for a long time.
Smart Images

Figure BDA0005159527410000061 
Figure BDA0005159527410000071 
Figure BDA0005159527410000072
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of engineering plastics, and more specifically, to a PBT composition and a preparation method and application thereof. Background Art
[0002] Polybutylene terephthalate (PBT resin) is a widely used crystalline polyester engineering plastic with excellent mechanical properties, heat resistance, electrical properties, solvent resistance, fatigue resistance and creep resistance. PBT resin has the characteristics of fast crystallization speed, short molding cycle, excellent dimensional stability and low water absorption, and is widely used in electronic and electrical, home appliances and automobile fields. Under normal circumstances, adding a certain amount of glass fiber to PBT material can meet customers' needs for the strength and toughness of parts. For example, in motor stators and rotors, air fryers, and new energy battery BDUs, glass fiber is basically needed to improve the strength and toughness of the material, thereby broadening its application scenarios. However, glass fiber reinforced PBT materials are exposed to strong sunlight for a long time, and the material is prone to aging and degradation, the glass fiber is exposed, the surface gloss of the part decreases, and yellowing occurs, which affects the appearance and performance of the material and limits its application.
[0003] In order to improve the color difference change of glass fiber reinforced PBT materials after aging, UV absorbers are usually added to reduce the influence of ultraviolet light on the materials to reduce the color difference of the materials after aging. As the UV absorber is added, the color difference after aging is reduced, but when the amount of UV absorber reaches a certain value, further increasing the amount of UV absorber does not significantly improve the reduction of the color difference after aging, so its application in products used outdoors for a long time, such as smart boat outboards, photovoltaic brackets, air conditioner outboard parts, new energy battery parts, etc. is limited. Therefore, the art needs to develop a PBT composition with a smaller color difference after aging and good mechanical properties. Summary of the invention
[0004] The purpose of the present invention is to provide a PBT composition to overcome the defects or shortcomings of the weather resistance of the glass fiber reinforced PBT composition in the prior art, such as insufficient color difference after aging and low mechanical properties.
[0005] Another object of the present invention is to provide a method for preparing the PBT composition.
[0006] Another object of the present invention is to provide application of the PBT composition.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] A PBT composition comprises the following components calculated by weight: 44-56 parts of PBT resin; 10-15 parts of ethylenebistetrabromophthalimide; 25-35 parts of glass fiber; 0.2-1.5 parts of ultraviolet light absorber; 0.1-2 parts of ultraviolet light shielding agent; the ultraviolet light absorber is a hindered amine light stabilizer.
[0009] The present invention adopts PBT resin as the base resin, selects ethylenebistetrabromophthalimide to cooperate with the ultraviolet light absorber and the ultraviolet light shielding agent, so that the PBT composition has good flame retardant performance, good weather resistance, and small color difference before and after aging.
[0010] It should be noted that the content of PBT resin in the PBT composition of the present invention is preferably not less than 40 wt.%.
[0011] It should be noted that the PBT resin described in the present invention is 44 to 56 parts, specifically 44 parts, 45 parts, 46 parts, 47 parts, 48 parts, 49 parts, 50 parts, 51 parts, 52 parts, 53 parts, 54 parts, 55 parts or 56 parts, all of which can realize the present invention.
[0012] The ethylenebistetrabromophthalimide of the present invention is 10 to 15 parts, specifically 10 parts, 10.5 parts, 11 parts, 11.5 parts, 12 parts, 12.5 parts, 13 parts, 13.5 parts, 14 parts, 14.5 parts or 15 parts, etc., which can realize the present invention.
[0013] The hindered amine light stabilizer of the present invention is 0.2 to 1.5 parts, specifically 0.2 parts, 0.25 parts, 0.3 parts, 0.35 parts, 0.4 parts, 0.45 parts, 0.5 parts, 0.55 parts, 0.6 parts, 0.65 parts, 0.7 parts, 0.75 parts, 0.8 parts, 0.85 parts, 0.9 parts, 0.95 parts, 1 parts, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts or 1.5 parts, etc., all of which can achieve the present invention.
[0014] The 0.1-2 parts of ultraviolet light shielding agent in the present invention can be 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, 1.9 parts or 2 parts, etc., all of which can achieve the present invention.
[0015] Furthermore, the mass ratio of the hindered amine light stabilizer to the ultraviolet light shielding agent is 1:(0.5-2.5).
[0016] Specifically, the mass ratio of the hindered amine light stabilizer to the ultraviolet light shielding agent can be 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:1, 1:1.1, 1:1.2:1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2, 1:2.1, 1:2.2, 1:2.3, 1:2.4 or 1:2.5, all of which can achieve the present invention.
[0017] The content of the hindered amine light stabilizer in the present invention is not less than 0.5wt% of the PBT composition.
[0018] Furthermore, the intrinsic viscosity of the PBT resin is 0.7 to 1.2 dL / g.
[0019] Furthermore, the intrinsic viscosity of the PBT resin is 0.75 to 0.9 dL / g.
[0020] Specifically, the testing standard for the intrinsic viscosity is ISO1628-5-2015.
[0021] Specifically, the hindered amine light stabilizer includes a tertiary amine hindered amine light stabilizer and / or a secondary amine hindered amine light stabilizer.
[0022] Specifically, the secondary amine hindered amine light stabilizer is N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-N,N'-diadehyde hexamethylenediamine and / or poly{[6-[(1,1,3,3-tetramethylbutyl)amino]]-1,3,5-triazine-2,4-[(2,2,6,6,-tetramethyl-piperidinyl)imino]-1,6-hexanediyl[(2,2,6,6-tetramethyl-4-piperidinyl)imino]}(LS-944).
[0023] The tertiary amine hindered amine light stabilizer is poly (4-hydroxy-2,2,6,6-tetramethyl-1-piperidinethanol-ALT-1,4-succinic acid).
[0024] Furthermore, the ultraviolet light absorber is a tertiary amine hindered amine light stabilizer. The use of this type of ultraviolet light absorber has the effect of better preventing the color change of the material surface.
[0025] Furthermore, the glass fiber is alkali-free chopped E glass fiber, with a fiber diameter of 7 μm to 15 μm and a length of 3 mm to 5 mm.
[0026] Furthermore, the PBT composition further comprises 2 to 6 parts of a flame retardant synergist and 1 to 5 parts of a toughening agent.
[0027] Furthermore, the toughening agent includes one or more of ethylene-acrylate, ethylene-acrylate-glycidyl ester, ethylene-octene copolymer, ethylene-octene copolymer-glycidyl ester or ethylene-vinyl acetate copolymer.
[0028] Furthermore, the synergistic flame retardant is an antimony-containing flame retardant, for example, antimony trioxide or sodium antimonate.
[0029] Specifically, the ultraviolet light shielding agent is titanium dioxide.
[0030] Specifically, the average particle size D50 of the titanium dioxide is 0.1 to 1.5 μm.
[0031] Specifically, the average particle size D50 is measured with reference to GB / T 19077.1-2016 standard.
[0032] Furthermore, the PBT composition also includes 0.1 to 5 parts of auxiliary agents.
[0033] Specifically, the auxiliary agent includes one or more of an antioxidant, a lubricant or an anti-dripping agent.
[0034] The antioxidant described in the present invention can be selected from commonly used antioxidants according to the prior art, such as but not limited to one or more of hindered phenol antioxidants, thioether antioxidants, hindered phenol antioxidants or diphenylamine antioxidants.
[0035] In a specific embodiment, the phosphite antioxidant is one or more of tris(2,4-di-tert-butylphenyl)phosphite (Irganox 168), bis(2,6-di-tert-butyl-4-tolyl) pentaerythritol phosphite (PEP-36) or 627A; the thioether antioxidant is one or more of distearyl thiodipropionate, dilauryl thiodipropionate or pentaerythritol dodecathiopropyl ester; the hindered phenol antioxidant is N,N'-hexamethylenebis(3,5-di-tert-butyl-4-hydroxyphenylpropionamide) (Irganox 1098), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (Irganox 1010), 1,6-hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] (Irganox259), β-(4-hydroxy-3,5-di-tert-butylphenyl) propionate n-octadecyl (Irganox 1076) or 3,9-bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl) acrylic acid]-1,1-dimethyl}-2,4,8,10-tetraoxaspirocycloundecane (ADK AO-80) or more thereof; the diphenylamine antioxidant is one of butyl / octyl diphenylamine and dioctyl diphenylamine.
[0036] The lubricant in the present invention can be selected from commonly used lubricants with reference to the prior art, such as but not limited to one or more of ester lubricants, amide lubricants, polyethylene lubricants or stearic acid lubricants.
[0037] Specifically, the ester lubricant is one or more of aliphatic stearate, oleic acid-based aliphatic polyester or medium-acid-based aliphatic polyester; the amide lubricant is one or more of erucamide, oleic acid amide or EBS; the polyethylene lubricant is one or more of polyethylene-acrylic acid copolymer wax A-C540, A-C580, A-C5120; the stearic acid lubricant is zinc stearate and / or calcium stearate.
[0038] Furthermore, the PBT composition comprises the following components calculated in parts by weight:
[0039] 48-52 parts of PBT resin; 11-14 parts of ethylenebistetrabromophthalimide; 3-5 parts of synergistic flame retardant; 28-32 parts of glass fiber; 2-4 parts of toughening agent; 0.3-0.8 parts of ultraviolet light absorber; 0.5-1.5 parts of ultraviolet light shielding agent; 0.5-1.5 parts of auxiliary agent.
[0040] The present invention also provides a method for preparing the PBT composition, comprising the following steps:
[0041] S1. The components of the above PBT composition except glass fiber, ethylene bis-tetrabromophthalimide and synergistic flame retardant are mixed to obtain a premix A; ethylene bis-tetrabromophthalimide and synergistic flame retardant are mixed to obtain a premix B;
[0042] S2. The premix A and premix B described in step S1 are fed into the extruder through the main feeding port, and the glass fiber is fed into the extruder through the side feeding port, and the PBT composition is obtained by mixing, dispersing, melt extruding and granulating.
[0043] Specifically, the mixing speed in step S1 is 600 to 900 rpm and the mixing time is 2 to 4 minutes.
[0044] Specifically, the extruder in step S2 is a twin-screw extruder.
[0045] Specifically, the temperature of zone 1 of the twin-screw extruder is 200-230°C, the temperature of zone 2 is 240-260°C, the temperature of zones 3 to 5 is 235-255°C, the temperature of zone 6 is 240-260°C, the temperature of zone 7 is 240-260°C, the temperature of zone 8 is 220-240°C, the temperature of zone 9 is 220-240°C, and the temperature of zone 10 is 240-260°C; the screw speed of the twin-screw extruder is 200-450 rpm.
[0046] The present invention also provides the use of the PBT composition in the preparation of household appliance parts, automobile parts, electronic and electrical parts, especially parts with long-term outdoor working conditions, such as smart boat outboard motors, photovoltaic brackets, air conditioner outboard parts, new energy battery parts and other materials.
[0047] Compared with the prior art, the present invention has the following beneficial effects:
[0048] The invention provides a PBT composition, which adopts glass fiber to enhance mechanical properties, selects ethylenebistetrabromophthalimide as a flame retardant, and cooperates with an ultraviolet light absorber to improve the color difference change of the PBT composition after aging, and the material has good flame retardant properties and mechanical properties. DETAILED DESCRIPTION
[0049] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.
[0050] 1. Raw materials used in various embodiments and comparative examples of the present invention:
[0051] PBT resin: PBT 1200-211M, viscosity 0.83 dL / g, purchased from Changchun Chemical (Jiangsu) Co., Ltd.;
[0052] Glass fiber: HMG436S-10-4.0, purchased from Taishan Glass Fiber Co., Ltd.;
[0053] Ethylene bis(tetrabromophthalimide):
[0054] Ethylene bis-tetrabromophthalimide 1: flame retardant BT-93W, purchased from Guangzhou Yuanda New Materials Co., Ltd.;
[0055] Ethylene bis(tetrabromophthalimide) 2: BR-951, purchased from Shouguang Wantai Chemical Co., Ltd.;
[0056] Other brominated flame retardants:
[0057] Brominated flame retardant 1: brominated epoxy flame retardant, F-2100, purchased from ICL, Israel;
[0058] Brominated flame retardant 2: brominated polystyrene, SAYTEX 621, purchased from Albemarle, USA;
[0059] Brominated flame retardant 3: polypentabromobenzyl acrylate, FR-1025, purchased from ICL, Israel;
[0060] Brominated flame retardant 4: brominated polycarbonate, FG-8500, purchased from Teijin;
[0061] Synergistic flame retardant: antimony white, S-05N, purchased from Foshan Chenti Economic and Trade Co., Ltd.;
[0062] Toughener: ethylene-acrylate-glycidyl methacrylate (EMA-GMA), PTW, purchased from DuPont;
[0063] UV absorber:
[0064] UV absorber 1: tertiary amine hindered amine light stabilizer, Tinuvin 622SF, purchased from BASF;
[0065] UV absorber 2: tertiary amine hindered amine light stabilizer, HALS-622, purchased from Suqian Liansheng Technology Co., Ltd.;
[0066] UV absorber 3: secondary amine hindered amine light stabilizer, HALS-944, purchased from Suqian Liansheng Technology Co., Ltd.;
[0067] UV absorber 4: benzotriazole UV absorber, UV-234, purchased from Suqian Liansheng Technology Co., Ltd.;
[0068] UV shielding agent: titanium dioxide, R103, purchased from DuPont;
[0069] Additives:
[0070] Antioxidant: antioxidant 1076, commercially available; Lubricant: ester lubricant, commercially available; It should be noted that the parallel experiments of various embodiments and comparative examples in the present invention all use the same raw materials.
[0071] 2. The PBT compositions described in the examples and comparative examples were prepared according to the formulations in Tables 1 to 2 by the following preparation method:
[0072] S1. The components other than glass fiber, ethylene bis-tetrabromophthalimide and synergistic flame retardant in the glass PBT composition were mixed at 700 rpm for 3 minutes to obtain a premix A; ethylene bis-tetrabromophthalimide and synergistic flame retardant were mixed at 800 rpm for 3 minutes to obtain a premix B;
[0073] S2. The premix A and premix B described in step S1 are fed through the main feeding port, and the glass fiber is fed into the twin-screw extruder through the side feeding port, and a composition is obtained by mixing, dispersing, melt extruding and granulating; the temperature of zone 1 of the twin-screw extruder is 215°C, the temperature of zone 2 is 250°C, the temperatures of zones 3 to 5 are 245°C, the temperature of zone 6 is 250°C, the temperature of zone 7 is 250°C, the temperature of zone 8 is 230°C, the temperature of zone 9 is 230°C, and the temperature of zone 10 is 250°C; the screw speed of the twin-screw extruder is 320 rpm.
[0074] 3. Performance Testing
[0075] (1) Tensile strength test: The PBT compositions prepared in each example and comparative example were tested according to standard ISO 527-2-2012;
[0076] (2) Izod notched impact strength: The PBT compositions prepared in the above examples and comparative examples were measured according to the ISO 180-2019 standard;
[0077] (3) Flame retardant performance test: The PBT compositions prepared in the above examples and comparative examples were tested according to the UL94-2013 vertical combustion standard with a thickness of 0.8 mm;
[0078] (4) Weathering performance test: The PBT compositions prepared in the above examples and comparative examples were placed in a UV aging chamber (power 20 W, wavelength range 315-400 nm) for continuous irradiation for 1000 hours. The changes in the L, a, and b values of the test samples before and after irradiation were measured to obtain ΔE; ΔE = (ΔL 2 +△a 2 +△b 2 ) 1 / 2 .
[0079] Examples 1 to 8 and Comparative Examples 1 to 7
[0080] Table 1 Amount (unit: weight parts) and properties of each component in the PBT composition in each embodiment
[0081]
[0082]
[0083] Table 2 Amount (unit: weight parts) and properties of each component in the PBT composition in each comparative example
[0084]
[0085] It can be seen from Table 1 that the PBT compositions prepared in the embodiments of the present invention have good weather resistance, small color difference change after aging, and good mechanical properties and flame retardant properties. Specifically, all embodiments can meet 0.8mmV-0 flame retardancy, meet the color difference before and after aging △E<10, preferably △E<5, and can meet the conditions of long-term outdoor use.
[0086] It can be seen from Comparative Example 1 that if only specific ethylenebistetrabromophthalimide is used without adding an ultraviolet light absorber, the weather resistance of the product is average, and the color difference ΔE before and after aging exceeds 10, which is significantly worse than that of the embodiment.
[0087] It can be seen from Comparative Examples 2 to 5 that the use of other types of flame retardants, even with the addition of ultraviolet light absorbers and ultraviolet light shielding agents, cannot meet the requirement of small color difference change after aging.
[0088] It can be seen from Comparative Example 6 that if other ultraviolet light absorbers are used, even if specific flame retardants and ultraviolet light shielding agents are added, the requirement of small color difference change after aging cannot be met.
[0089] It can be seen from Comparative Example 7 that if only the ultraviolet light absorber is used, the requirement of small color difference change after aging cannot be met.
[0090] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A PBT composition, characterized in that: The invention comprises the following components calculated by weight: 44-56 parts of PBT resin; 10-15 parts of ethylenebistetrabromophthalimide; 25-35 parts of glass fiber; 0.5-1.5 parts of ultraviolet light absorber; 0.1-2 parts of ultraviolet light shielding agent; the ultraviolet light absorber is a hindered amine light stabilizer.
2. The PBT composition according to claim 1, characterized in that: The hindered amine light stabilizer includes a secondary amine hindered amine light stabilizer and / or a tertiary amine hindered amine light stabilizer.
3. The PBT composition according to claim 1, characterized in that: The toughening agent includes one or more of ethylene-acrylate, ethylene-acrylate-glycidyl ester, ethylene-octene copolymer, ethylene-octene copolymer-glycidyl ester or ethylene-vinyl acetate copolymer.
4. The PBT composition according to claim 1, characterized in that: The hindered amine light stabilizer is poly{[6-[(1,1,3,3-tetramethylbutyl)amino]]-1,3,5-triazine-2,4-[(2,2,6,6,-tetramethyl-piperidinyl)imino]-1,6-hexanediyl[(2,2,6,6-tetramethyl-4-piperidinyl)imino]} and / or poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol-ALT-1,4-succinic acid).
5. The PBT composition according to claim 1, characterized in that: The mass ratio of the ultraviolet light absorber to the ultraviolet light shielding agent is 1:(0.5-2.5).
6. The PBT composition according to claim 1, characterized in that: The ultraviolet light shielding agent is titanium dioxide.
7. The PBT composition according to claim 1, characterized in that: It also includes 2 to 6 parts of synergistic flame retardants and 1 to 5 parts of toughening agents.
8. The PBT composition according to claim 1, characterized in that: It also includes 0.1 to 5 parts of auxiliary agents.
9. A method for preparing the PBT composition according to any one of claims 1 to 8, characterized in that: The steps include: S1. The components of the above PBT composition except glass fiber, ethylene bis-tetrabromophthalimide and synergistic flame retardant are mixed to obtain a premix A; ethylene bis-tetrabromophthalimide and synergistic flame retardant are mixed to obtain a premix B; S2. The premix A and premix B described in step S1 are fed into the extruder through the main feeding port, and the glass fiber is fed into the extruder through the side feeding port, and the PBT composition is obtained by mixing, dispersing, melt extruding and granulating.
10. Use of the PBT composition according to any one of claims 1 to 8 in the preparation of household appliance parts, automobile parts, and electronic and electrical parts.
Citation Information
Patent Citations
PBT composition as well as preparation method and application thereof
CN112679916A
High-PTI high-toughness PBT composition as well as preparation method and application thereof
CN112778710A
Good-appearance glass fiber reinforced flame-retardant PBT (polybutylene terephthalate) composition as well as preparation method and application thereof
CN114517004A
High-impact long-acting yellowing-resistant PBT (polybutylene terephthalate) reinforced flame-retardant composite material as well as preparation method and application thereof
CN114773798A
Polybutylene terephthalate resin composition as well as preparation method and application thereof
CN120098418A
Cited By
PBT composition, and preparation method therefor and use thereof
WO2026114294A1